Econometric approach to evaluating national competitiveness - Vasenkova, Elena I.; Kazak, Anastasia A. (Journal of the Belarusian State University. Economics, 2019)
The authors consider various approaches to evaluate the level of national competitiveness. The factors determining the level of national competitiveness form the basis for building econometric models of competitiveness indices according to the methods of the World Economic Forum and the International Institute for Management Development. Forecasting values of the national competitiveness index of the Republic of Belarus are counted based on the models developed.